High renin hypertension in focal renal fibromuscular dysplasia: turn off of renin system angiotensin overactivation by renal angioplasty cured high blood pressure and quickly reversed myocardial hypertrophy. - Merla, Simona; Simoni, Riccardo; Tedeschi, Stefano; Ferrari, Massimiliano; Passeri, Giovanni; Marcato, Carla; Epifani, Enrico; Semproni, Ignazio; Zini , Giulia; Verzicco, Ignazio; Coghi, Pietro; Volpi, Riccardo; et al. (Acta Biomedica Atenei Parmensis, 2021)
Background Fibromuscolar dysplasia (FMD) is an idiopathic, non-atherosclerotic and non-inflammatory stenotic lesion of renal arteries causing renovascular hypertension up-regulating renin-angiotensin-aldosterone system. Case report: A 18-year-old man was referred to our Hypertension Center (Clinica e Terapia Medica) for the recent onset of hypertension, poorly controlled on calcium channel blockers, already associated to electrocardiographic and echocardiography signs of left ventricular hypertrophy and significant albuminuria (728 mg/24 h). An increased plasma renin activity (PRA), aldosterone level and a mild hypokalemia raised the suspicion of renovascular hypertension. Abdominal CT and MRI angiography showed mild kidneys asymmetry and a tubular stenosis of the right renal artery in its mid-distal portion close to renal hilum. Radionuclide renal scintigraphy documented a kidneys asymmetry of separated glomerular filtration rate. Renal FMD was diagnosed based on patient age and the absence of cardiovascular risk factors for atherosclerosis. Patient successfully underwent right renal angioplasty giving a rapid normalization of blood pressure levels without antihypertensive drugs. Plasma aldosterone and PRA rapidly normalized as well as serum potassium levels. Six months after angioplasty echocardiography showed a regression of left ventricular hypertrophy and the patient albumin urine excretion became normal (14 mg/24 h). Conclusions FMD can cause renovascular hypertension associated to organ damage such myocardial hypertrophy and albuminuria through mechanisms dependent but also independent from blood pressure levels. Renal angioplasty turned off renin-angiotensin-aldosterone overactivity allowing the cure the hypertension and a surprisingly rapid reverse of myocardial hypertrophy and of excess of albumin urine excretion not only dependent on blood pressure normalization.